2017
DOI: 10.3171/2016.2.jns152059
|View full text |Cite
|
Sign up to set email alerts
|

A long-term study of durability and risk factors for aneurysm recurrence after microsurgical clip ligation

Abstract: OBJECTIVE With the recent evolution of endovascular therapies, objective evaluation of the efficacy of clip ligation for cerebral aneurysms should be performed. This study was undertaken to evaluate the durability of microsurgical clip ligation, identify risk factors for recurrence, and assess the need for long-term follow-up imaging. METHODS A retrospective review of medical records identified 616 consecutive patients (156 male and 460 female patients; mean age 48.4 ± 12.4 years; range 6-90 years) who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 22 publications
0
26
0
3
Order By: Relevance
“…Although aneurysm clipping is associated with high rates of initial occlusion and durability,16 17 these rates remain imperfect and inflated by the use of non-invasive postoperative imaging. Critical residual or recurrent components of an aneurysm can be missed (figures 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although aneurysm clipping is associated with high rates of initial occlusion and durability,16 17 these rates remain imperfect and inflated by the use of non-invasive postoperative imaging. Critical residual or recurrent components of an aneurysm can be missed (figures 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…7 Of note, the presence of multiple aneurysms has been identified as a risk factor for de novo aneurysm formation in prior reports. [1][2][3]18 The presence of multiple aneurysms was a strong and independent predictor of AO aneurysms in our cohort (42.0% vs 20.0%, OR…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have demonstrated the efficacy of microsurgical clip ligation in the treatment of cerebral aneurysms through long-term follow-up angiography, with a 0.14% recurrence rate of nearly 700 clipped aneurysms without residua [9]. Bohnstedt et al investigated 319 cases of ACoA aneurysms treated with microsurgical clip ligation [8].…”
Section: Discussionmentioning
confidence: 99%